Development of 9kWp solar system to enhance smoked shrimp (sesar unjur) production at Igan, Sarawak, Malaysia - Kasumawati, Lias; Hazrul, Mohamad Basri; Yonis M Yonis, Buswig; Annisa, Jamali; Abang Mohammad Nizam, Abang Kamaruddin; Siti Kudnie, Sahari (Elsevier Ltd., 2024)
This paper presents a reliable stand-alone solar Photovoltaic (SAPV) system to supply the electricity needs of the sesar unjur production, which is mainly to operate the 5 kW smoked machine. At the present time, the production is merely traditional by burning white mangrove wood to smoke fresh shrimp and give a unique taste to the sesar unjur. The traditional technique leads to low quantity production making it hard to penetrate a wider market. Therefore, a more automatised and modern technique should be adopted to increase the yield to production time ratio. The activities that were carried out during this work include load demand profile, a study of resource availability, sizing of PV panels and dimensioning of the hybrid solar PV inverter. The activities englobe the common steps of designing a stand-alone solar PV system. The detailed calculation of the sizing of the components mainly based on the Malaysia Sustainable Energy Development Authorities (SEDA) and MS standards. As a result, a SAPV system with total capacity of 9kWp from 20 solar PV panels, which is used to power up a 5 kW drying and smoking machine, is designed and installed at the targeted location where it agreed by the community. Based on the outcomes, the smoked solar machine (OGsAnuh) can produce 40 kg sesar unjur per day, which requires around 400 kg of fresh shrimp or known as payak, by the local people. This is carried out in 4 cycles of production, with each cycle process about 100 kg fresh shrimp, which results in 10 kg sesar unjur. Furthermore, the dense of smoked taste can be controlled, which significant to market demand and environmental sustainability, simultaneously.